Endovascular Embolization of Ruptured Infundibular Dilation of Posterior Communicating Artery: A Case Report - Jinlu Yu; Honglei Wang; Kan Xu; Bai Wang; Qi Luo (Case Reports in Medicine)
Hemorrhage due to the rupture of the infundibular dilatation of the posterior communicating artery (ID of the PCo-A) occurs infrequently. The preferred treatment of such hemorrhages is surgical clipping through craniotomy. There are few reports about endovascular coil embolization in such cases. We report such a case treated by endovascular embolization. A 35-year-old man, who had experienced 2 episodes of subarachnoid hemorrhage (SAH), was found to have a ruptured ID of the PCo-A by head computed tomography angiography (CTA) and digital subtraction angiography (DSA). We performed stent-assisted endovascular coil embolization through a combined anterior and posterior circulation approach. Postembolization angiography showed absence of contrast filling of the ID of the PCo-A and nonleakage of the contrast agent. The patient recovered well with no complications. SAH recurrence was not recorded during the 1-year followup. The postoperative angiographic result was good. To our knowledge, this is the first case of hemorrhage due to ruptured ID of the PCo-A that was treated by such a technique.